Do the characteristics of online consumer reviews bias buyers' purchase intention and product perception? A perspective of review quantity, review quality and negative review sequence. (1st January 2013) - Zhou, Ming; Liu, Mengwei; Tang, Dingna
Online consumer product reviews have long been considered an important form of electronic word-of-mouth (eWOM) and have generated widespread interests in business research fields. The reviews provide potential buyers with product comments and evaluations from a user's perspective, which is generally believed to be neutral and impartial. However, little research explored the bias in the process of potential buyers' browsing reviews. This paper examines how the sequence of negative reviews, the quantity of online feedback text and the quality of online comments affect consumer purchase intention. The experiment's results suggest that the quantity and quality of online consumer product reviews have a positive effect on consumer purchase intention. However, consumers show a negativity bias for products when negative consumer reviews concentrate in the foreground.